Ответы и объяснения

2013-05-27T18:10:23+00:00

1. а-х(а-х)+а+х(а+х)/ (а+х)(а-х)=2а+2х^2/(а+х)(а-х)

2. 2а+2х^2/(а+х)(а-х)* а^2+x^2/(а+х)(а-х)= все сокращается и остается 2

Лучший Ответ!
2013-05-27T18:12:08+00:00

 

(a-x) ^ 2 + (a+x)^ 2            (a-x) (a+x)                       a^2 - 2a x + x^2 +   a^2 + 2a x + x^2      

 (a+x) * (a-x)               *           a^2  + x^2      =                       a^2  + x^2                                         =

 

 

      2   a^2  + 2 x^2                           2(   a^2 + x^2  )      

=         a^2  + x^2                      =          a^2  + x^2           =    2